COMPOSITION, STRUCTURE, AND CARBON SEQUESTRATION OF DIFFERENT RAINFOREST ECOSYSTEMS IN THE GUNUNG GEDE PANGRANGO NATIONAL PARK, INDONESIA - Agus Sunyata; Isna Rakhmi Zulhida; Nike Triwahyuningsih; Kanda Raharja (SEAMEO BIOTROP, 2024)
ARTICLE HIGLIGHTS- High demand for environmental services makes the park vulnerable to human activities.- Both ecosystems are well regenerated; seedling > sapling > pole > tree (inverted J)- Both ecosystems show normal diversity conditions and stable species distribution.- Growth of Maesopsis eminii needs monitoring to preserve forest purity.- Montane forests have greater biomass, carbon stocks, less anthropogenic disturbanceABSTRACTThe Gunung Gede Pangrango National Park (GGPNP) area is one of the vital ecosystems that support the environment in West Java Province, Indonesia. It is a unique area that has multiple forest ecosystems, including lowland rainforest and montane rainforest ecosystems. Despite the GGPNP’s status as a conservation area, the high demand for the GGPNP’s environmental services makes the region vulnerable to disturbances from human activities. Several studies have been conducted in the GGPNP area (lowland and montane forest ecosystems), however, the results of this study are still necessary to explain the forest dynamics and forest carbon sequestration in this location. The objective of this research was to analyze the structure, composition, and carbon sequestration of stands in the lowland and montane rainforest ecosystems in the GGPNP area. Data processing and analyses were conducted using diversity indices, biomass-carbon stock estimation, and carbon dioxide sequestration estimation. The results showed that the GGPNP lowland and montane rainforest ecosystems were well regenerated. The number of seedlings > saplings > poles > trees and the graph showed a reverse “J” pattern. The GGPNP lowland rainforest ecosystem was dominated by Neonauclea lanceolata and had relatively higher species diversity. The GGPNP montane rainforest ecosystem was dominated by Castanopsis acuminatissima with a higher individual density, denser canopy, and more complex canopy strata. The lack of regeneration in several species of trees heightens the threat to these species’ existence in the future. Biomass, carbon stocks, and carbon sequestration in the GGPNP montane rainforest were greater than those in the GGPNP lowland rainforest. The GGPNP montane rainforest ecosystem had older forest stands, a larger average tree diameter, and lower potential for anthropogenic disturbances.